Peningkatan Skill Productivity Bagi Pengrajin Batu Piring di Desa Sukowiryo Kecamatan Jelbuk Kabupaten Jember - Lilis Yuliati; Siti Komariyah; Sudarsono Sudarsono (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
Plate stone handicraft products are one of the leading commodities and also potential for Sukowiryo Village, Jelbuk District, Jember Regency. Apart from being a superior commodity and village potential, plate stone handicraft products are also an export commodity. However, most of the plate stone handicraft production process in Sukowiryo Village still uses simple tools and manual processes. Therefore, the production process takes a longer time and the quality of the production is not standardized. The purpose of this PPK service activity is to provide real solutions to problems in the production process that connect by partners so that partners can increase skill productivity so that partners can carry out efficiency and can increase their production. The results of the KDP service activities were; 1) provide assistance to increase Skill Productivity by providing assistance with plate stone cutting machines according to partner needs. Build sewer and air reservoirs, and increase the partner's electric power to operate the plate stone cutting machine. 2) Partners can make time efficiency in the production process. 3) Partners can increase their productivity, 4) Partners can add 1 type of product diversification. 5) Carry out monitoring and evaluation after the program is implemented